Itineraires Therapeutiques Des Malades De L’ulcere De Buruli Et Difficultes De Prise En Charge Hospitaliere A Djekanou (Cote d’Ivoire) - Abel, Adjet A. (European Scientific Journal, ESJ, 2017)
Among the neglected tropical disease, Buruli ulcer (BU) is a real public health problem in Côte d’Ivoire. Facing this pathology, international and national institutions to combat advocate for people in endemic areas early detection and immediate use of support centers at the first signs. However, patients continue to attend late care centers with large ulcerative lesions. Therefore, healing requires a long-term hospitalization that requires medical and surgical treatment. The main objective of this study is to analyze the factors that change the therapeutic route of BU patients and constraints socio - economic issues related to their hospitalisation. This is a qualitative and quantitative study. We used the technique of reasoned choice. It covered 55 patients met at the Djekanou care center in the Toumodi Health District. Data were collected through structured and semi - structured interviews based on questionnaires, individual interview guides and focus groups. A significant proportion of patients with BU are children and adolescents. The sick are accompanied by a parent who takes care of them. Awareness campaigns, community health workers, television and radio did not really help to change the therapeutic itinerary of patients. The patients encountered testify to the ineffectiveness of traditional care. The hospitalization of patients is marked by difficulties of several kinds.